Bilateral benign cystic teratoma of ovary concomitant with an occult gall bladder carcinoma in a post-menopausal woman - Mandrelle, Kavita; Bhatti, Sahir (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Mature cystic teratomas are the most common benign germ cell tumours, and commonly seen in the reproductive age group. It rarely occurs in postmenopausal women. We report a case of bilateral dermoid cyst with cholelithiasis and occult gall bladder carcinoma in a postmenopausal woman.